Segregation of face sensitive areas within the fusiform gyrus using global signal regression? A study on amygdala resting‐state functional connectivity. Issue 10 (14th July 2015) - Kruschwitz, Johann D.; Meyer‐Lindenberg, Andreas; Veer, Ilya M.; Wackerhagen, Carolin; Erk, Susanne; Mohnke, Sebastian; Pöhland, Lydia; Haddad, Leila; Grimm, Oliver; Tost, Heike; Romanczuk‐Seiferth, Nina; Heinz, Andreas; et al.
Abstract The application of global signal regression (GSR) to resting‐state functional magnetic resonance imaging data and its usefulness is a widely discussed topic. In this article, we report an observation of segregated distribution of amygdala resting‐state functional connectivity (rs‐FC) within the fusiform gyrus (FFG) as an effect of GSR in a multi‐center‐sample of 276 healthy subjects. Specifically, we observed that amygdala rs‐FC was distributed within the FFG as distinct anterior versus posterior clusters delineated by positive versus negative rs‐FC polarity when GSR was performed. To characterize this effect in more detail, post hoc analyses revealed the following: first, direct overlays of task‐functional magnetic resonance imaging derived face sensitive areas and clusters of positive versus negative amygdala rs‐FC showed that the positive amygdala rs‐FC cluster corresponded best with the fusiform face area, whereas the occipital face area corresponded to the negative amygdala rs‐FC cluster. Second, as expected from a hierarchical face perception model, these amygdala rs‐FC defined clusters showed differential rs‐FC with other regions of the visual stream. Third, dynamic connectivity analyses revealed that these amygdala rs‐FC defined clusters also differed in their rs‐FC variance across time to the amygdala. Furthermore, subsample analyses of three independent research sites confirmed reliability of the effect of GSR, as revealed by similar patterns of distinct amygdala rs‐FC polarity within the FFG. In this article, we discuss the potential of GSR to segregate face sensitive areas within the FFG and furthermore discuss how our results may relate to the functional organization of the face‐perception circuit. Hum Brain Mapp 36:4089–4103, 2015. © 2015 Wiley Periodicals, Inc.